A study on hollow effect and safety design of deep crossing caverns under blasting vibration. (May 2021) - Xu, Mingnan; Li, Xinping; Liu, Tingting; Luo, Yi; Huang, Junhong; Wang, Gang; Wang, Yang; Gao, Wei
Highlights: Hollow amplification effect of blasting vibration is studied at deep crossing caverns. The most vulnerable locations of the surrounding rock are found. The modified Sadowski's formula considering the hollow effect is proposed. Abstract: Due to the spatial complexity of deep underground cavern group, the safety of crossing caverns during blasting excavation is attracting more and more attention. This article presents a systematic study on the effect of blasting excavation on the crossing caverns and surrounding rocks, based on the firsthand data from the main powerhouse and pressure pipelines of Baihetan Hydroelectric Power Station in China. Through the on-site blasting test and numerical simulation on the powerhouse, the vibration velocity and dynamic stress of surrounding rock under different blasting sources and different maximum explosive quantities are analyzed, the dynamic response characteristics of blasting vibration on the straight sidewalls and the opening of crossing caverns are obtained, and a modified formula for calculating the maximum explosive quantities that consider hollow effect is proposed. The study shows that, the blasting vibration velocity of the powerhouse is highest in the axial direction, followed by the transverse and vertical direction. The peak particle velocity ( PPV ) generally decreases with the increase of distance to the explosion center, whereas the hollow amplification effect at the openings of pressure pipelines is prominent (can be as high as 41.8% for this case). When the blasting zone is from 1.25 times of the cavern diameter in front of the pressure pipeline to the opening of caverns, the influence of hollow effect on the vibration of pressure pipeline is significant. The worst blasting location is the wall footing of the pressure pipeline that facing the blasting. The maximum vibration velocity, maximum tensile stress, and maximum shear stress on the opening mainly locate at the arch footing, the middle of straight sidewall, and the baseplate. In addition, the maximum tensile stress ratio was greater than the maximum shear stress ratio, indicating that the opening of the crossing cavern is more susceptible to tensile failure. The modified formula considering hollow effect is successfully applied in the blasting design of this project, which can provide experiences and references for the design and construction of similar deep-buried crossing caverns.